PENERAPAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK DIKUSI DALAM MENINGKATKAN RASA PERCAYA DIRI PADA PESERTA DIDIK KELAS VII MTs DARUNADWAH DI MASA PANDEMI COVID 19 - Widuri Faizah Rahmah Faizah; Mustika, R. Ika; Fatimah, Siti (IKIP Siliwangi, 2024)
Group guidance services are a form of assistance provided by guidance and counseling teachers or counselors to a number of students through group activities. The problems in this personal-social include relationship problems with fellow friends, with teachers, problems of self-nature and ability, good self-confidence in the educational environment and the community in which they live and conflict resolution. For students who have problems regarding lack of self-confidence in school, it is appropriate to give, because the problems they experience are related to personal-social. The technique that can be given is using discussion techniques, because it is a way in which students get the opportunity to solve problems together. Each student has the opportunity to present a problem. The purpose of this study was to determine the implementation and response in the implementation of group guidance services for students who have self-confidence problems. The approach used in this study is a qualitative descriptive approach with phenomenological methods. Data collection techniques used are observation, interviews and documentation. The results of the study indicate that group guidance services using discussion techniques are effective because they provide an understanding of the importance of being confident in school and provide direction so that students are more confident.